2013
DOI: 10.1007/s00415-013-7051-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of tafamidis for the treatment of transthyretin familial amyloid polyneuropathy

Abstract: Tafamidis, a transthyretin (TTR) kinetic stabilizer, delayed neuropathic progression in patients with Val30Met TTR familial amyloid polyneuropathy (TTR-FAP) in an 18-month randomized controlled trial (study Fx-005). This 12-month, open-label extension study evaluated the long-term safety, tolerability, and efficacy of tafamidis 20 mg once daily in 86 patients who earlier received blinded treatment with tafamidis or placebo. Efficacy measures included the Neuropathy Impairment Score in the Lower Limbs (NIS-LL),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
314
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(332 citation statements)
references
References 32 publications
12
314
0
4
Order By: Relevance
“…6). A similar outcome could potentially be achieved with chemical chaperones, which have been used to mitigate the misfolding and toxicity of other amyloidogenic proteins (52). Either with small molecules or alternative approaches, our results advocate for concealing the C4F6 epitope and/or stabilizing loops IV and VII as rational therapeutic strategies for SOD1-mediated ALS.…”
Section: Discussionmentioning
confidence: 57%
“…6). A similar outcome could potentially be achieved with chemical chaperones, which have been used to mitigate the misfolding and toxicity of other amyloidogenic proteins (52). Either with small molecules or alternative approaches, our results advocate for concealing the C4F6 epitope and/or stabilizing loops IV and VII as rational therapeutic strategies for SOD1-mediated ALS.…”
Section: Discussionmentioning
confidence: 57%
“…At the end of the extension study, neurologic function was better preserved among patients who continuously received tafamidis than among those who received 18 months of placebo followed by 12 months of tafamidis, and underscores the benefit of early intervention [22,23]. A 12-month open-label study in 21 non-ATTRV30M patients further demonstrated the generalizability of the TTR-stabilizing effect, and indicated clinical efficacy of tafamidis for delaying disease progression across several other TTR variants [24].…”
Section: Introductionmentioning
confidence: 89%
“…An 18-month, double-blind, randomized, placebocontrolled study of tafamidis in 128 ATTRV30M patients with early stage ATTR-FAP and its subsequent 12-month open-label extension study demonstrated the safety and efficacy of tafamidis in delaying the progression of polyneuropathy [21,22]. At the end of the extension study, neurologic function was better preserved among patients who continuously received tafamidis than among those who received 18 months of placebo followed by 12 months of tafamidis, and underscores the benefit of early intervention [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of FAP TTR Met 30, there are two therapeutical options that significantly alter the psychological burden imposed by this condition: FAP-I patients are offered Tafamidis (Coelho et al 2013) which may delay the progression of the disease or liver transplantation (Rolim et al 2006). The patients and their families now see FAP-I as being less threatening than other neurodegnerative diseases such as SCA3 and HD (Rolim et al 2006;Paneque et al 2009;Ledo et al 2013), and this may increase the presymptomatic testing uptake.…”
Section: Atxn2 Gene Large Normal Allelesmentioning
confidence: 99%